Pengaruh Gaya Hidup, Ulasan Pelanggan, dan Kualitas Pelayanan Terhadap Keputusan Pembelian Pada Marketplace Tiktok Shop (Studi Kasus Pada Mahasiswa Fakultas Ekonomi dan Bisnis Di Kota Lamongan) - Muhammad Dzikri Abadi; Siti Hajar Falasifa Nirmala; Dadang Wiratama; M Adhitya Nugraha Pratama (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
This study aims to analyze the influence of lifestyle, customer reviews, and service quality on purchasing decisions on the TikTok Shop marketplace. This research employs a quantitative approach with lifestyle, customer reviews, and service quality as independent variables, and purchasing decisions as the dependent variable. The population as well as the sample of this study consisted of 98 students from the Faculty of Economics and Business in Lamongan City who use TikTok Shop, selected using a non-probability sampling technique. The data used were primary data collected through an online questionnaire survey using Google Forms. Data analysis was conducted using the Partial Least Squares (PLS) method with the assistance of SmartPLS 3 software through structural model (inner model) testing. The results indicate that lifestyle, customer reviews, and service quality have a positive and significant effect on purchasing decisions, both partially and simultaneously. These findings suggest that lifestyle preferences, information obtained from customer reviews, and service quality play an important role in influencing consumer purchasing decisions on social media–based marketplace platforms. This study is expected to contribute theoretically to the development of consumer behavior studies and serve as a reference for future research related to purchasing decisions in digital marketplaces.